The Hamlet murders : a Zhong Fong mystery - Rotenberg, David (Toronto, McArthur, 2004)
Summary: Fong investigates the apparent suicide of his dead wife's lover, a Canadian theatre director found hanging from a rope in the Shanghai Theatre Academ
Keywords: Detective and mystery fiction; China -- Shanghai